Diffraction of optical beams by a half-plane - Anokhov, S.; Khizhnyak, A.; Lymarenko, R. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2000)
Rigorous solution of the optical beam diffraction problem on half plane is represented. Solution is described to representation of edge dislocation wave (EDW) that was introduced for describing the diffraction plane wave on half plane. It is shown that in problem of diffraction EDW plays the role of eigenmode as plane wave in free space. Due to this the solving of mentioned problem reduces to calculation of convolution of angle spectrum of source beam and EDW.